Phase equilibrium data and methods: implication of present state on heavy petroleum fractions and coal processing. Part II: The equation of state approach to predicting vapor -liquid equilibrium - Zudkevitch, D. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The need to produce liquid fuel and chemical fuel stocks from heavy and highly aromatic petroleum fractions, residues, and coal poses he questions whether the existing hermodynamic data correlations are applicable and what new data should be measured. Evaluations of existing correlations as to their applicability to the conditions of processing coal fluids and heavy oil are presented in a series of four articles. Such evaluations are considered important in planning the measurement of new data and further research. In this second article of the series, the equation of state approach to predicting vapor-liquid equilibrium is discussed.